Dysbiotic Bacterial and Fungal Communities Not Restricted to Clinically Affected Skin Sites in Dandruff - Soares, Renan C.; Camargo-Penna, Pedro H.; de Moraes, Vanessa C. S.; De Vecchi, Rodrigo; Clavaud, Cécile; Breton, Lionel; Braz, Antonio S. K.; Paulino, Luciana C. (Frontiers in cellular and infection microbiology, 2016)
Dandruff is a prevalent chronic inflammatory skin condition of the scalp that has been associated with yeasts. However, the microbial role has not been elucidated yet, and the etiology of the disorder remains poorly understood. Using high-throughput 16S rDNA and ITS1 sequencing, we characterized cutaneous bacterial and fungal microbiotas from healthy and dandruff subjects, comparing scalp and forehead (lesional and non-lesional skin sites). Bacterial and fungal communities from dandruff analyzed at genus level differed in comparison with healthy ones, presenting higher diversity and greater intragroup variation. The microbial shift was observed also in non-lesional sites from dandruff subjects, suggesting that dandruff is related to a systemic process that is not restricted to the site exhibiting clinical symptoms. In contrast, microbiota analyzed at species level did not differ according to health status. A 2-step OTU assignment using combined databases substantially increased fungal assigned sequences, and revealed the presence of highly prevalent uncharacterized organisms (>37% of the reads). Although clinical symptoms of dandruff manifest locally, microbial dysbiosis beyond clinically affected skin sites suggests that subjects undergo systemic alterations, which could be considered for redefining therapeutic approaches.